2005
DOI: 10.1007/s11101-005-2494-9
|View full text |Cite
|
Sign up to set email alerts
|

Plants as a Source of Bacterial Resistance Modulators and Anti-Infective Agents

Abstract: The spread of multidrug-resistant (MDR) strains of bacteria necessitates the discovery of new classes of antibacterials and compounds that inhibit these resistance mechanisms. At present, there are no single chemical entity plant-derived antibacterials used clinically, and this chemically diverse group deserves consideration as a source for two major reasons. First, plants have exceptional ability to produce cytotoxic agents and second there is an ecological rationale that antimicrobial natural products should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(135 citation statements)
references
References 53 publications
(41 reference statements)
4
119
0
8
Order By: Relevance
“…It has been assumed that if present trends continue, antibiotic failure will claim 10 million lives per year by 2050 (O'Neill 2014). Therefore, there has been increasing interest in the role of inhibitors of antibiotic resistance for combination therapy (Gibbons 2005, Wright 2005). Nanotechnology represents a modern and forward-looking approach to develop new formulations based upon metallic nanoparticles with antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…It has been assumed that if present trends continue, antibiotic failure will claim 10 million lives per year by 2050 (O'Neill 2014). Therefore, there has been increasing interest in the role of inhibitors of antibiotic resistance for combination therapy (Gibbons 2005, Wright 2005). Nanotechnology represents a modern and forward-looking approach to develop new formulations based upon metallic nanoparticles with antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…First, plants have exceptional ability to produce cytotoxic agents and second there is an ecological rationale that antimicrobial natural products should be present or plants following microbial attack to protect the producer from pathogenic microbes in its environment. 22 We have previously shown that dietary phenolic compounds are effective against the intracellular bacterium C. pneumoniae. 17,18 As it has been proposed that natural compounds in combination with antibiotics could be a new strategy for developing therapies for infections caused by bacterial species and that natural plant products can potentiate the activity of antibiotics in combination, 23,24 we wanted to investigate whether coadministration of phenolic compounds with the antichlamydial compound doxycycline results in synergistic inhibition of acute C. pneumoniae infection.…”
Section: Discussionmentioning
confidence: 99%
“…The use of natural antibiotics from plants does not induce side effects such as abdominal pain, diarrhea, cramping, headache, nausea and vomiting. Plant products may be used as antibiotic alternatives and do not cause resistance in bacteria [5].…”
Section: Introductionmentioning
confidence: 99%